Strange matter in core-collapse supernovae - Sagert, Irina; Hempel, Matthias; Schaffner-Bielich, Jürgen (Acta physica Polonica. B, Particle physics and field theory, nuclear physics, theory of relativity, 2012)
We discuss the possible impact of strange quark matter on the evolution of core-collapse supernovae with emphasis on low critical densities for the quark-hadron phase transition. For such cases the hot proto-neutron star can collapse to a more compact hybrid star configuration hundreds of milliseconds after core-bounce. The collapse triggers the formation of a second shock wave. The latter leads to a successful supernova explosion and leaves an imprint on the neutrino signal. These dynamical features are discussed with respect to their compatibility with recent neutron star mass measurements which indicate a stiff high density nuclear matter equation of state.